Analisis Wacana Jurnalisme Investigasi Dalam Film Nothing Uncovered - Meirani Fatmawati; Sumaina Duku; Jufrizal . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
The phenomenon of investigative journalism portrayed in the Korean drama *Nothing Uncovered* illustrates the dynamics of media, power, and truth amid social conflicts and political interests. The drama shows how the search for facts goes beyond the surface of news reporting, touching upon courage, ethics, and the professional dilemmas faced by journalists. Based on this phenomenon, this study aims to analyze the representation of investigative journalism practices in the drama using Teun A. Van Dijk’s Critical Discourse Analysis (CDA) approach. This research employs a qualitative descriptive method with audiovisual text analysis. Data were collected through documentation of key scenes depicting investigative activities, then analyzed using van Dijk’s three dimensions: text structure, social cognition, and social context. The findings reveal that *Nothing Uncovered* represents investigative journalism as a layered process, starting from evidence collection, witness interviews, to news publication under pressure from power structures. At the textual level, the drama emphasizes discourse strategies that contrast truth with media manipulation. On the level of social cognition, the journalist is portrayed as an agent of change who adheres to justice and integrity. Meanwhile, at the social context level, the drama illustrates the power relations between media, law, and politics, which often restrict press freedom. This study highlights that the representation of investigative journalism in popular media not only provides entertainment but also serves as a critical reflection of social realities and the challenges faced by the press profession in society.